Fertility properties and regulation of antimicrobial substance production by plasmid SCP2 of Streptomyces coelicolor. - Troost, T R (1979)
Streptomyces coelicolor A3(2) possesses two plasmids (SCP1 and SCP2) that act as sex factors. The plasmid deoxyribonucleic acid isolated from S. coelicolor A3(2) SCP1- strains A617 and A585 had the same molecular weight and endonuclease cleavage pattern as the SCP2 plasmid. The plasmidless strain S18 SCP2- was isolated from the A617 X A585 cross. SCP2 plasmid-containing strains acted as donors of chromosomal markers, whereas the plasmidless strain acted as recipient. The transfer of SCP2+ donor strain markers into the SCP2- recipient occurred at high frequencies (approximately 75%), was unidirectional, was initiated from a fixed region of the chromosome, and had the SCP2 fertility factor transferred first. The introduction of the SCP2 plasmid into a recipient strain greatly reduced the recombination frequency. These fertility properties differed from those previously reported, thereby suggesting that the SCP2 plasmid examined in this investigation may be an additional variant to those described in the literature. The SCP2 plasmid also regulated production of three antibacterial substances and conveyed resistance for S. coelicolor A3(2) strains against growth inhibition by one of them.